Effect of immunization registry-based provider reminder to initiate HPV vaccination at age 9, Washington state - Trevor Christensen; Sherri Zorn; Kathy Bay; Katherine Treend; Chrystal Averette; Nicole Rhodes (Human Vaccines & Immunotherapeutics)
Human papillomavirus (HPV) vaccination rates are lower than Tetanus-diphtheria-pertussis (Tdap) and Meningococcal conjugate (MenACWY) rates, although the Advisory Committee on Immunization Practices recommends all three vaccines be given routinely at age 11–12. Evidence is mounting that children who initiate HPV vaccination starting at age 9 are more likely to complete the series on time. Washington state implemented a provider reminder through its immunization information system (WAIIS) in January 2023 to increase HPV vaccine initiation at 9-years-old by updating the forecasted recommended age for HPV from age 11 to 9. The effectiveness of provider reminders when implemented via an immunization information system (IIS) is poorly understood. We evaluated the impact of this forecast update using a seasonally adjusted interrupted time series regression of weekly HPV initiations at 9-years-old before and after implementation. We also examined time series trends of vaccine administration between 2018 and 2023 for HPV initiation at age 9, as well as Tdap, MenACWY and HPV initiation at age 11. The WAIIS forecast update doubled the weekly rate of HPV initiation among 9-year-olds in Washington state, although the weekly count of initiation at 9 remains far lower than initiations at 11. Jurisdictions wanting to increase HPV vaccine initiation at earlier ages should consider updating their forecast algorithm and investing in complementary evidence-based strategies such as provider and parent education, and clinic-based quality improvement efforts. The reach of IIS forecaster updates may be enhanced by working with administrators of electronic medical record systems to ensure parity of provider prompts with IIS.